2021
DOI: 10.1136/jnnp-2021-326337
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes of spinal cord grey and white matter following spinal cord injury

Abstract: ObjectivesTraumatic and non-traumatic spinal cord injury produce neurodegeneration across the entire neuraxis. However, the spatiotemporal dynamics of spinal cord grey and white matter neurodegeneration above and below the injury is understudied.MethodsWe acquired longitudinal data from 13 traumatic and 3 non-traumatic spinal cord injury patients (8–8 cervical and thoracic cord injuries) within 1.5 years after injury and 10 healthy controls over the same period. The protocol encompassed structural and diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…A clinical neurophysiological and MRI studies indicated the development of these events in distant areas of patients’ spinal cord after spinal cord injury. Distinct spatiotemporal dynamics of tissue-specific neurodegeneration were found above and below spinal cord injury ( David et al, 2021 ). Spatiotemporal experimental analysis of the gray and white matter of the spinal cord at a distance from the epicenter of injury shows the differential pattern and severity of pathological reactions, gene expression, and molecular regulation in the remote rostral and caudal regions ( Ek et al, 2010 ; Yu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A clinical neurophysiological and MRI studies indicated the development of these events in distant areas of patients’ spinal cord after spinal cord injury. Distinct spatiotemporal dynamics of tissue-specific neurodegeneration were found above and below spinal cord injury ( David et al, 2021 ). Spatiotemporal experimental analysis of the gray and white matter of the spinal cord at a distance from the epicenter of injury shows the differential pattern and severity of pathological reactions, gene expression, and molecular regulation in the remote rostral and caudal regions ( Ek et al, 2010 ; Yu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…After SCI, the primary injury triggers a cascade of pathophysiological processes at the focal injury site ( Ahuja et al, 2017 ) with subsequent secondary disease processes (i.e. anterograde, retrograde, and trans-synaptic degeneration) ( David et al, 2021 , David et al, 2019 , David et al, 2022 , Freund et al, 2019 , Freund et al, 2013b , Grabher et al, 2015 , Lundell et al, 2011 , Seif et al, 2018a , Seif et al, 2020 , Ziegler et al, 2018 ). Histopathological evidence illustrates that at the earliest stage post-SCI axonal swelling and myelin thinning can be detected at the lesion border ( Brennan et al, 2013 , Bresnahan, 1978 , Bresnahan et al, 1976 , Buss et al, 2005 , Grumbles and Thomas, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…SCI causes local damage to the tissue and leads to the secondary pathological cascade, such as spatiotemporal changes in gray and white matter atrophy . Studies reported longitudinal changes in gray and white matter composition after the spinal cord injury . The white matter contains the axonal trajectories, which can be misinterpreted as the regenerated fibers while present as the spared axons.…”
Section: Introductionmentioning
confidence: 99%